1999
DOI: 10.21236/ada370293
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Protective Mask Seal Pressure to Fit Factor and Head Harness Strap Stretch

Abstract: at Baltimore (UMAB), for his interest in and willingness to guide and support her research efforts. She would also like to thank David Harrah, Human Research and Engineering Directorate (HRED) of the U.S. Army Research Laboratory (ARL), for his expert guidance in the use and study of protective masks, as well as for an extensive review of her manuscript. The author would like to thank many others who provided assistance along the way: Ronald Carty, ARL, for his skilled preparation of photos and illustrations; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Thus, in the current mask design process, many important decisions are made before designers evaluate the most critical performance requirement, protection. Cohen [3] demonstrated that measuring and evaluating the pressure distribution between the mask sealing surface and face provides valuable information about seal integrity. Cohen also determined relationships between head harness strap stretch (a measure of strap tightness) and either FF or seal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the current mask design process, many important decisions are made before designers evaluate the most critical performance requirement, protection. Cohen [3] demonstrated that measuring and evaluating the pressure distribution between the mask sealing surface and face provides valuable information about seal integrity. Cohen also determined relationships between head harness strap stretch (a measure of strap tightness) and either FF or seal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study of the surface contact pressures was performed by HRED (Cohen, 1996) and was used during this effort as a means of validating the simulation. In this experiment, contact pressures were measured at thirty degree intervals around the face.…”
Section: Resultsmentioning
confidence: 99%
“…Cohen [3] described an experimental method for evaluating mask seals by measuring seal pressure distributions. A relationship between FF and sealing pressure distributions for evaluating the sealing performance was developed.…”
Section: Contact Pressure Study Of N95 Filtering Face-piece Respiratomentioning
confidence: 99%